2015
DOI: 10.3389/fncel.2015.00461
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Hypertension Aggravates Innate Immune Responses after Experimental Stroke

Abstract: Arterial hypertension is not only the leading risk factor for stroke, but also attributes to impaired recovery and poor outcome. The latter could be explained by hypertensive vascular remodeling that aggravates perfusion deficits and blood–brain barrier disruption. However, besides vascular changes, one could hypothesize that activation of the immune system due to pre-existing hypertension may negatively influence post-stroke inflammation and thus stroke outcome. To test this hypothesis, male adult spontaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 87 publications
1
23
0
Order By: Relevance
“…These results suggest that chronic systemic hypertension deregulates microglial responses and support the importance of injury-induced activation of microglia. In contrast, infiltrating peripheral leukocytes were correlated with the extent of injury in hypertension [237], demonstrating the detrimental function of periphery-derived mononuclear phagocytes. The involvement of mononuclear phagocytes in hypertension-induced exacerbation of stroke outcomes and mortality suggests an immunological explanation for this risk factor.…”
Section: Hypertensionmentioning
confidence: 90%
“…These results suggest that chronic systemic hypertension deregulates microglial responses and support the importance of injury-induced activation of microglia. In contrast, infiltrating peripheral leukocytes were correlated with the extent of injury in hypertension [237], demonstrating the detrimental function of periphery-derived mononuclear phagocytes. The involvement of mononuclear phagocytes in hypertension-induced exacerbation of stroke outcomes and mortality suggests an immunological explanation for this risk factor.…”
Section: Hypertensionmentioning
confidence: 90%
“…As for the effect of diabetes, the explanation is that diabetes involves chronic systemic low-grade inflammation manifested by reactive oxygen species generation, proinflammatory cytokines expression, and other inflammatory mediator activation (28). The finding surrounding hypertension could be explained by increased numbers and activation status of circulating myeloid leukocytes and increased levels of leukocyte-attracting chemokines (13).…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that in the experimental mouse model of diabetes, acute inflammatory responses are perturbed in the brain following stroke, and the alteration is associated with the exacerbation of stroke-induced injury (12). Moreover, an animal experiment observes that pre-existing hypertension causes larger stroke sizes possibly as consequence of a profound increase of post-stroke inflammation (13).…”
Section: Introductionmentioning
confidence: 99%
“…Important risk factors for stroke such as arterial hypertension or hyperlipidemia cause a chronic activation of the innate and adaptive arm of the immune system. These changes successively disrupt vascular function leading to cerebral small vessel disease and atherosclerosis . Moreover, a pre‐activated immune system aggravates stroke severity and outcome .…”
Section: Immune System Mattersmentioning
confidence: 99%